2013
DOI: 10.1161/circimaging.112.975193
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Imaging of Inflammation and Platelet Adhesion in Advanced Atherosclerosis Effects of Antioxidant Therapy With NADPH Oxidase Inhibition

Abstract: Background In atherosclerosis, local generation of reactive oxygen species amplifies the inflammatory response and contributes to plaque vulnerability. We used molecular imaging to test whether inhibition of NADPH oxidase with apocynin would reduce endothelial inflammatory activation and endothelial-platelet interactions, thereby interrupting progression to high-risk plaque phenotype. Methods and Results Mice deficient for both the LDL receptor and Apobec-1 were studied at 30 weeks of age and again after 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 43 publications
2
64
0
Order By: Relevance
“…1 Accumulating evidence indicates that AS is the result of a prolonged and excessive inflammatory process in the vascular wall, which often begins with inflammatory changes in the endothelium, characterized by the expression of adhesion molecules. [2][3][4] Pharmaceutical and dietary strategies have targeted these disorders to control AS, and many natural products with excellent pharmacological properties are good candidates for the control or prevention of AS. [5][6][7][8] Resveratrol inflammation participates centrally in all stages of atherosclerosis (as), which begins with inflammatory changes in the endothelium, characterized by expression of the adhesion molecules.…”
Section: Introductionmentioning
confidence: 99%
“…1 Accumulating evidence indicates that AS is the result of a prolonged and excessive inflammatory process in the vascular wall, which often begins with inflammatory changes in the endothelium, characterized by the expression of adhesion molecules. [2][3][4] Pharmaceutical and dietary strategies have targeted these disorders to control AS, and many natural products with excellent pharmacological properties are good candidates for the control or prevention of AS. [5][6][7][8] Resveratrol inflammation participates centrally in all stages of atherosclerosis (as), which begins with inflammatory changes in the endothelium, characterized by expression of the adhesion molecules.…”
Section: Introductionmentioning
confidence: 99%
“…5,19,20 Thus, the greater improvement in coronary microcirculatory function and improvement in arterial wall properties may have also contributed to the greater improvement in LV function in our patients with CAD compared with their non-CAD counterparts.…”
Section: Effects Of Il-1 Inhibition On LV Function In Cad Versus Non-cadmentioning
confidence: 91%
“…IL-1 induces NADPH oxidase expression, 18 leading to reactive oxygen species production which in turn reduces endothelial function and favors artery vasoconstriction. 19,20 Therefore, we may speculate that a larger IL-1-driven oxidative burden may have contributed to the lower FMD and CFR observed in our patients with CAD compared with those without CAD.…”
Section: Baseline Differences Between Ra Patients With and Without Cadmentioning
confidence: 91%
“…Consistent with this hypothesis are the data from another study conducted in patients with peripheral artery disease, which is a marker of systemic atherosclerosis; in that study, patients with peripheral artery disease were characterized by upregulation of NADPH oxidase activation, which was associated with lowered flow-mediated dilatation and enhanced intima-media thickness. 3 The study conducted in CGD patients is also useful in the interpretation of another interesting finding by Liu et al, 1 that is, the inhibition of platelet adhesion to the atherosclerotic plaque by apocynin treatment. Platelets from CGD had an almost complete absence of reactive oxidant species production and impaired platelet production of isoprostanes, which are proaggregating eicosanoids derived from the interaction of arachidonic acid with reactive oxidant species.…”
Section: To the Editormentioning
confidence: 97%
“…Liu et al 1 have recently demonstrated that, in an animal model of atherosclerosis, apocynin, an inhibitor of nicotinamide adenine dinucleotide phosphate (NADPH) oxidase, halted atherosclerotic progression with a mechanism involving reduced monocyte infiltration and platelet adhesion; animals prone to atherosclerosis were also characterized by impaired artery elasticity, which was reversed by apocynin treatment. These data show that atherosclerotic progression is associated with impaired artery elasticity and suggest that inhibition of NADPH oxidase may favorably affect both.…”
Section: To the Editormentioning
confidence: 99%